Quantitation of amyloid beta peptides Aβ₁–₃₈, Aβ₁–₄₀, and Aβ₁–₄₂ in human cerebrospinal fluid by ultra-performance liquid chromatography–tandem mass spectrometry - Lame, Mary E; Chambers, Erin E; Blatnik, Matthew (Analytical biochemistry, 2011)
Critical events in Alzheimer’s disease (AD) involve an imbalance between the production and clearance of amyloid beta (Aβ) peptides from the brain. Current methods for Aβ quantitation rely heavily on immuno-based techniques. However, these assays require highly specific antibodies and reagents that are time-consuming and expensive to develop. Immuno-based assays are also characterized by poor dynamic ranges, cross-reactivity, matrix interferences, and dilution linearity problems. In particular, noncommercial immunoassays are especially subject to high intra- and interassay variability because they are not subject to more stringent manufacturing controls. Combinations of these factors make immunoassays more labor-intensive and often challenging to validate in support of clinical studies. Here we describe a mixed-mode solid-phase extraction method and an ultra-performance liquid chromatography tandem mass spectrometry (SPE UPLC–MS/MS) assay for the simultaneous quantitation of Aβ₁–₃₈, Aβ₁–₄₀, and Aβ₁–₄₂ from human cerebrospinal fluid (CSF). Negative ion versus positive ion species were compared using their corresponding multiple reaction monitoring (MRM) transitions, and negative ions were approximately 1.6-fold greater in intensity but lacked selectivity in matrix. The positive ion MRM assay was more than sufficient to quantify endogenous Aβ peptides. Aβ standards were prepared in artificial CSF containing 5% rat plasma, and quality control samples were prepared in three pooled CSF sources. Extraction efficiency was greater than 80% for all three peptides, and the coefficient of variation during analysis was less than 15% for all species. Mean basal levels of Aβ species from three CSF pools were 1.64, 2.17, and 1.26ng/ml for Aβ₁–₃₈; 3.24, 3.63, and 2.55ng/ml for Aβ₁–₄₀; and 0.50, 0.63, and 0.46ng/ml for Aβ₁–₄₂.